TERAPI ES KRIM BAWANG PUTIH MEMPENGARHI PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI DESA KEMIRI SIDOARJO - Hidayatus Sya’diyah; Meiana Harfika; Maria Yesika Radya (Jurnal Ilmiah Kesehatan, 2014)
Condition when the systolic blood pressure over 120 mmHg and diastolic over 80 mmHg. Suspected of garlic ice cream can lower high blood pressure in hypertensive patients if given by mouth one time a day. This study aims to analyze the effect of garlic ice cream therapy to lower blood pressure in hypertensive patients in the Kemiri village of Sidoarjo.Design used quasy-experimental. With non equivalent control group design. The population is hypertensive patients who suffer from hypertension. The sample are 24 hypertensive patients selected by non probality sampling approach to purposive sampling. Research uses the blood pressure observation sheet instruments. Data were analyzed using paired t-test.The research results obtained before blood pressure given garlic ice cream most respondents included in the classification of mild hypertension in experimental group and the rest of the respondents included in the classification of mild hypertension in the control group. Blood pressure therapy after being given ice cream garlic whole respondents included in the classification of normotensi on experimental group.And including the classification of hypertension mild in all respondents the control group. The results of the test independent t-test obtained p = 0,000 It means that there are differences in rates of systolic and diastolic blood pressure beetwen experimental and control groups after the intervention of garlic ice cream.